2011
DOI: 10.3892/ijo.2011.1218
|View full text |Cite
|
Sign up to set email alerts
|

Tubeimoside-1 induces G2/M phase arrest and apoptosis in SKOV-3 cells through increase of intracellular Ca2+ and caspase-dependent signaling pathways

Abstract: Abstract. Tubeimoside-1 (TBMS1) extracted from Bolbostemma paniculatum (Maxim), is a traditional Chinese herb with anticancer potential. It induces apoptosis in a number of human carcinoma cell lines, but the mechanism has remained unclear.In the present study, we investigated the pro-apoptotic activity of TBMS1 against SKOV-3 cell lines and the underlying mechanisms. Treatment with TBMS1 resulted in dose-and time-dependent inhibition of proliferation, led to arrest in phase G 2 /M of the cell cycle and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“… 22 , 25 It has been reported that ERK1/2 regulates the expression of Bcl-2, which partly contributes to the presumption that ERK1/2 is the upstream effector of Bcl-2. 29 Consistent with the available studies, our data pointed out that various concentrations of TBMS1 increased c-PARP expression, accompanied by the decrease in total PARP expression after cells were treated with high doses of TBMS1, and TBMS1 markedly inhibited p-ERK1/2 expression, which leads to the Bcl-2 product decline in this study. Therefore, our results revealed that TBMS1 might induce intrinsic apoptosis through the ERK1/2/Bcl-2/caspase-9/caspase-3/PARP pathway, and the extrinsic apoptotic pathway was also involved in cellular apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“… 22 , 25 It has been reported that ERK1/2 regulates the expression of Bcl-2, which partly contributes to the presumption that ERK1/2 is the upstream effector of Bcl-2. 29 Consistent with the available studies, our data pointed out that various concentrations of TBMS1 increased c-PARP expression, accompanied by the decrease in total PARP expression after cells were treated with high doses of TBMS1, and TBMS1 markedly inhibited p-ERK1/2 expression, which leads to the Bcl-2 product decline in this study. Therefore, our results revealed that TBMS1 might induce intrinsic apoptosis through the ERK1/2/Bcl-2/caspase-9/caspase-3/PARP pathway, and the extrinsic apoptotic pathway was also involved in cellular apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“… 7 , 8 TBMS1 induces G2/M phase arrest and apoptosis in ovarian cancer cells through an increase in intracellular Ca 2+ levels and caspase-dependent signaling. 9 TBMS1 inhibited human choriocarcinoma cancer cell proliferation by inducing Cytochrome C release and apoptosis via the mitochondrial-related signaling pathway. 10 TBMS1 inhibits proliferation and induces apoptosis by increasing the Bax to Bcl-2 ratio and decreasing COX-2 expression in lung cancer cells.…”
Section: Introductionmentioning
confidence: 94%
“…Tubeimoside-1 can also sensitize cell response to cisplatin in cisplatin-resistant human ovarian cancer cells (A2780/DDP) through down-regulation of ERK and up-regulation of p38 (Liu H. Z. et al, 2011). Tubeimoside-1 increased the expression of CHOP and phosphorylated p38, resulting in G 2 /M phase arrest and apoptosis in SKOV-3 human ovarian carcinoma cells (Chen W. J. et al, 2012). In addition, tubeimoside-1 can induce oxidative stress-mediated apoptosis and G 2 /M phase arrest in HepG2 liver cancer cells via NF-κB, JNK, and p53 pathways (Yin et al, 2011).…”
Section: Components Isolated From Tcms That Inhibit Mapkmentioning
confidence: 99%